Plasticity of trophic interactions in fish assemblages results in temporal stability of benthic-pelagic couplings. (August 2021) - Timmerman, Charles-André; Giraldo, Carolina; Cresson, Pierre; Ernande, Bruno; Travers-Trolet, Morgane; Rouquette, Manuel; Denamiel, Margaux; Lefebvre, Sébastien
Abstract: This study addresses the temporal variability of couplings between pelagic and benthic habitats for fish assemblages at five periods in a shallow epicontinental sea, the Eastern English Channel (EEC). Organic matter fluxes fueling fish assemblages and the relative contribution of their different sources were assessed using stable isotope analysis and associated isotopic functional metrics. Couplings between benthic and pelagic realms appeared to be a permanent feature in the EEC, potentially favored by shallow depth and driven by the combination of two trophic processes. First, trophic interactions exhibited plasticity and revealed resource partitioning. Second, changes in the composition of fish assemblages did not impact benthic-pelagic couplings, as most dominant species were generalists during at least one time period, allowing complete use of available resources. Examining both unweighted and biomass-weighted indices was complementary and permitted a better understanding of trophic interactions and energy fluxes. Highlights: Most fish species displayed trophic plasticity over time. Trophic resources were used optimally through complementarity. When considering biomass, dominant species were trophic generalists. Couplings between benthic and pelagic habitats are a permanent feature of the EEC.